Kairo, Ägypten: Die Geschichte der Abteilung Kairo des DAI im Spannungsfeld deutscher politischer Interessen von 1881 bis 1966 - Voss, Susanne (e-Forschungsberichte des DAI, 2023)
The scientific-historical project about “The History of the German Institute in Cairo amidst political interests in the time from 1881 to 1966” is coming to its conclusion. The second volume, examining the end of the Weimar Republic, NS Period and Afterwar Period, visualizes both scientific-political and historical-epistemological lines of continuity in German egyptology, and at the DAI. A further focus involves the establishing of German-Egyptian cooperation in archaeology. The book is planned to appear in 2017.